The effect of creative acceleration strategy on creative thinking abilities of talented students in Saudi Arabia - Abdeen, Samar; Ewies, Mahmoud (Jurnal Pendidikan Bitara UPSI, 2019)
This study aimed at assessing the role of the Creative Acceleration Strategy in enhancing the creative thinking abilities of talented students. Quasi-Experimental approaches were used to examine the effect of the Creative Acceleration Strategy on creative thinking abilities.  60 talented students consisting of were surveyed from the Taibah University in Saudi Arabia.  The sampled sixty talented students were divided equally into two groups; control and experimental. Torrance tests were adopted to assess the students’ creative thinking abilities in the pre and post-application of the regular Creative Acceleration Strategy. Data were collected using quantitative (experimental) approach. The findings showed a significant difference between the control and experimental groups (after intervention) with regards to the development of the creative thinking abilities of the students.  Also, the findings indicated that the students thinking abilities were significantly enhanced after the application of Creative Acceleration Strategy.  This study confirmed that creative thinking abilities can be enhanced through specialized strategies directed at the development of creative thinking abilities.